FASHION INSPIRING FROM ARCHITECTURE; A WORKSHOP AT ARCHITECTURAL DESIGN STUDIO: ARCHIFASHION - Yildiz, Selin; Duzgun, Hande (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2014)
World is changing and architects no longer design only buildings but also clothing, shoes for well known brands. On the other side, fashion activities are much keen on architecture and fashion shows are organised that are inspiring from architecture. Using the concentration between two disciplines, architecture and fashion can be said to have much in common as using design concepts to generate forms. Concepts help to read the idea behind the design and have an idea for the new ones. Also focusing concepts is essential in architecture because strong concepts could build new and strong ways of seeing the world. Architectural education has hybrid disciplines including art and technical knowledge. Although students complain about hard technical courses, Architectural Design courses show the lack of strong design concepts. In that point Archi-Fashion Design titled concept is chosen for this study as a key tool for searching design inspiration in an informal way. Aim of the study is to improve a methodology for discovering architectural inspiration by transition between different art branches. The isolation from technical education by workshop environment made students feel as fashion designers for creative ideas. The study consists of 3 modules; 1.information and research, 2.Abstraction and 3.Product Design. First, fashion designers used their theoretical background which they gained from Basic Design Course at first year education. Afterwards, they made some researches about fashion design, designers and shows. Finally, they used the expressions of chosen architectural design in the form of clothing by designing, practicing and presenting. The method of the study was helpful to students to be successful in connections, abstractions, concepts, forms and ideas. They gained to see the architectural product in a differential manner, to understand the idea behind the design which is orientated by design principles through a conceptual study.
Keywords: Abstraction; Concepts; Fashion Design; Architectural Design; Art and Architecture; Education & Educational Research